Determinants of Reproductive Health Behaviour Among Female Workers in Tertiary Institutions in Southwestern Nigeria (2014)
Women reproductive health behaviour (RHB) has generated a lot of interest from researchers across many disciplines because many women die due to pregnancy related complications. Hence, improving RHB of women which is a key aspect of the Millennium Development Goals requires a proper understanding of its predisposing factors. Previous studies on women’s RHB had focused more on adolescents, rural and non-literate women without due consideration to women in the tertiary institutions. This study, therefore, examined the extent to which gender roles, age at marriage, educational attainment, peer influence, mass media exposure, cultural norms/religious belief and socio-economic status influenced the RHB of female workers in tertiary institutions in Southwestern Nigeria. The survey research design was adopted. The purposive sampling technique was used to select 1,122 respondents: 540 academic and 582 non-academic female workers from five universities, four polytechnics and four colleges of education in Southwestern Nigeria. Two instruments were used: RHB Scale (r=0.81) and RHB Determinants Scale with seven sub-scales, socio-economic status (r=0.79), cultural/religious belief (r=0.83), mass media (r=0.75), gender role (r=0.79) and peer influence (r=0.71). Nine Focus Group Discussions (FGDs) and two In-depth interview (IDI) sessions were conducted with female workers from each of the 13 institutions. Four research questions were answered and eight hypotheses tested at 0.05 level of significance to determine the RHB of female workers. Data were analysed using percentages, multiple regression, Pearson product moment correlation and content analysis. Seventy-five percent of respondents exhibited good RHB. The seven predisposing factors had joint positive significant prediction on female workers’ (RHB) in tertiary institutions (F(7,1114) = 520.091; R = 0.875, R2 =0.766, Adj.R2 = 0.764) and accounted for 77.0% in the variance of the dependent measure. Their relative contributions were: gender roles (β=.404), age at marriage (β=.320), educational attainment (β=.191), peer influence (β=-.161), mass media exposure (β=-.122), cultural norms/religious belief (β=-.094)) and socio-economic status (β=-.091). Also, their significant strength of relationships with RHB were as ranked: age at marriage (r=0.740), gender role (r=0.738), educational attainment (r=0.426), religious/cultural belief (r=0.092); mass media exposure (r=0.085), social economic status (r=-0.739) and peer influence (r=-0.541). There was no significant difference in the RHB of female academic and non-academic staff in all the institutions sampled. Participants’ knowledge of reproductive health information varies from: menstruation and management (11.9%), safe motherhood and childcare (9.9%), family planning and contraception (9.7%) and pregnancy and childbirth (8.9%). Family gender roles in reproductive health decision making were perceived to inhibit women’s abilities to make informed reproductive health decisions. Mass media exposure, gender roles, age at marriage, socio-economic status, peer influence, cultural norms/religious belief and educational attainment strongly predicted reproductive health behaviour of female workers in sampled tertiary institutions. However, to ensure improved reproductive health behaviour among tertiary institutions female workers, there is the need to strengthen the use of mass media complemented with women’s networking groups and religious institutions aimed at promoting better reproductive health behaviour.